Decentralized Secure Online Digital Data Registrations - Dugyala, Raman; Hanuman Reddy, N; G, Raghuram; Lakshminarayana, J (International Journal of Engineering and Technology, 2018)
A potential challenge in the present secure transaction lies in illegitimate access to premium digital data available in various formats on various service-sectors for Government and Non-Government process models. This vulnerable scenario leads to identity attacks, man in the middle (MITM) attacks and denial of service (DoS) attacks. Our proposed model uses blockchain technology with machine learning classifiers to identify and detect possible attacks within a peer-to-peer network. Blockchain uses digital signatures, proof-of-work algorithm and consensus algorithms to protect system from possible integrity and denial of service attacks and machine learning classifiers deployed at every node offers confrontation to any intruderâ€™s attack.Â